Heart-rate responses by playing position during ball drills in basketball - Delextrat, A.; Kraiem, S. (International Journal of Sports Physiology and Performance, 2013)
The physiological load experienced during basketball drills is crucial to understand players` adaptation to team-sport training and plan physical-conditioning programs. Purpose: To compare mean heart-rate (HRmean) responses by playing position during 2-a-side (2v2) and 3-a-side (3v3) ball drills in male junior basketball players and explore the relationship between HRmean and repeated-sprint ability (RSA). Methods: Thirtyone players volunteered to participate in this study. On separate occasions, they performed 2v2 and 3v3 ball drills and 6 repetitions of shuttle-run sprints of 20 m (10+10 m), departing every 20 s (RSA). Ball drills took place on the full length but only half the width of the court and were three 4-min bouts separated by 1-min rest periods. An analysis of variance (ANOVA) assessed the effect of the number of players on court (2v2 vs 3v3) and playing position (guards vs forwards vs centers) on HRmean, and a Pearson correlation coefficient evaluated the relation between HRmean and RSA. Results: The main results showed greater HRmean in 2v2 than in 3v3 ball drills (P < .001) in all playing positions (90.7% ± 1.3% vs 87.6% ± 3% of HRpeak in guards, 91.3% ± 2.1% vs 87.5% ± 3.7% of HRpeak for forwards, and 88.2% ± 3.5% vs 82.2% ± 5.6% of HRpeak in centers, respectively, for 2v2 and 3v3). In addition, centers were characterized by lower HRmean than guards and forwards in 3v3 only (P = .018). Conclusions: These results suggest that 2v2 drills should be preferred to 3v3 drills for aerobic conditioning, in particular for centers. Finally, RSA does not seem to influence players` acute responses to ball drills.